Naturaleza, Literatura y Derecho: “El hombre que plantaba árboles” de J. Giono y la Sentencia de la Corte Suprema de Justicia de Colombia dictada con motivo de la deforestación de la Amazonía (Papeles, 2021)
In this work they are analyzed: a literary work, «The man who planted trees» by Jean Giono (1954); and the ruling of the Supreme Court of Justice of Colombia (2018), issued on the occasion of the deforestation of the Amazon. The degradation of Nature and the regeneration of its life cycles are addressed. In the literary work, the difficult task is faced by a man alone; while in the sentence the means are managed from the State. Thus, the argument lines of the ruling are explored and reflected in the light of the narrative on intergenerational equity and the rights of nature; forming a lighter vehicle of legal content to reach more people in society.